2010
DOI: 10.1002/chem.201001686
|View full text |Cite
|
Sign up to set email alerts
|

An Adamantyl Amino Acid Containing Gramicidin S Analogue with Broad Spectrum Antibacterial Activity and Reduced Hemolytic Activity

Abstract: The cyclic cationic antimicrobial peptide gramicidin S (GS) is an effective topical antibacterial agent that is toxic for human red blood cells (hemolysis). Herein, we present a series of amphiphilic derivatives of GS with either two or four positive charges and characteristics ranging between very polar and very hydrophobic. Screening of this series of peptide derivatives identified a compound that combines effective antibacterial activity with virtually no toxicity within the same concentration range. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 86 publications
(42 reference statements)
1
52
1
Order By: Relevance
“…The adamantylated analog 41 (Scheme 7) “…emerges as the most promising compound because of its ability to distinguish, at a specific concentration, between bacteria and mammalian cells.” 108 …”
Section: “Add-on” To Known Pharmaceuticalsmentioning
confidence: 99%
“…The adamantylated analog 41 (Scheme 7) “…emerges as the most promising compound because of its ability to distinguish, at a specific concentration, between bacteria and mammalian cells.” 108 …”
Section: “Add-on” To Known Pharmaceuticalsmentioning
confidence: 99%
“…[9] Alternatively, slight alterations in one or both b-turns have been introduced; for example, it was found that the d-phenylalanine residue may be substituted by a hydrophobic d-amino acid [10] or a dehydroamino acid [11] in order to retain the cyclic b-hairpin structure and hence the antibacterial activity. Incorporation of d-cyclo-hexylalanine, [12] however, led to an almost complete loss of antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…27 However, its clinical applications are limited to topical uses like ear infections,28 because GS is toxic for human red blood cells by causing hemolysis. Recent studies have shown that the hemolytic activity of GS‐based compounds can be tuned through modifications in the amino acid sequence; this has given rise to GS derivatives with decreased hemolytic properties, which retain antibacterial activity and the clinical applications of which as antibiotics are currently under investigation 29. 30…”
Section: Introductionmentioning
confidence: 99%
“…Four interstrand hydrogen bonds stabilize a special arrangement of the amino acids, with the hydrophobic amino acids side chains (Leu and Val) oriented to one side of the β‐sheet and the polar side chains (Orn) on the opposite side, which makes GS an amphiphilic molecule (Figure 2). 33, 34 Structural studies of native GS ( 1 ) and the analogues 4 – 8 (see Figures 5 and 9) with 1 H and 13 C NMR spectroscopy were described in recent papers 29. 3436 The dispersion of the amide proton signals in the 1 H NMR spectrum indicated that there are no multiple conformations in solution, and the observed chemical shifts, coupling constants, and nuclear Overhauser effects demonstrated that this conformation corresponds to a stable cyclic β‐hairpin configuration.…”
Section: Introductionmentioning
confidence: 99%